Synthesis of electrophile-tethered preQ1 analogs for covalent attachment to preQ1 RNA - Flemmich, Laurin; Micura, Ronald (Beilstein Journal of Organic Chemistry, 2025)
The preQ1 cIass-I riboswitch aptamer can utilize 7-aminomethyl-7-deazaguanine (preQ1) ligands that are equipped with an electrophilic handle for the covalent attachment of the ligand to the RNA. The simplicity of the underlying design of irreversibly bound ligand–RNA complexes has provided a new impetus in the fields of covalent RNA labeling and RNA drugging. Here, we present short and robust synthetic routes for such reactive preQ1 and (2,6-diamino-7-aminomethyl-7-deazapurine) DPQ1 ligands. The readily accessible key intermediates of preQ0 and DPQ0 (both bearing a nitrile moiety instead of the aminomethyl group) were reduced to the corresponding 7-formyl-7-deazapurine counterparts. These readily undergo reductive amination to form the hydroxyalkyl handles, which were further converted to the haloalkyl or mesyloxyalkyl-modified target compounds. In addition, we report hydrogenation conditions for preQ0 and DPQ0 that allow for cleaner and faster access to preQ1 compared to existing routes and provide the novel compound DPQ1.
Keywords: deazapurines; heterocycles; pyrrolopyrimidines; queuosine; riboswitches; ribozymes; RNA alkylation; RNA labelling